LITERATURE REVIEW: EVALUASI EFEKTIVITAS SUPLEMEN PROBIOTIK DALAM MENINGKATKAN KUALITAS SUSU SAPI PERAH - Badat Muwakhid; Camal Adi Maskur; Umi Kalsum; Usman Ali (Jurnal Agriovet, 2024)
This article reviews the effectiveness of probiotic supplements in improving the quality of dairy cow milk with the aim of providing a deep understanding of their impact on milk production and livestock health. Through a literature search from academic databases such as PubMed, ScienceDirect, and Google Scholar, as well as analysis of recent journal articles and research reports, it was found that probiotics can significantly enhance the protein content, fat content, and microbiological stability of milk, as well as improve the balance of intestinal microflora and immune response in cows. Although research results show positive benefits, there is variation in the effectiveness of probiotics influenced by the type of probiotic, dosage, frequency of administration, and farm management conditions. The conclusion of this review is that probiotics have great potential to improve milk quality, but further research is needed to optimize their use under various farming conditions.